AutodE: Automated Calculation of Reaction Energy Profiles— Application to Organic and Organometallic Reactions. Issue 8 (22nd December 2020) - Young, Tom A.; Silcock, Joseph J.; Sterling, Alistair J.; Duarte, Fernanda
Abstract: Calculating reaction energy profiles to aid in mechanistic elucidation has long been the domain of the expert computational chemist. Here, we introduce autodE (https://github.com/duartegroup/autodE ), an open‐source Python package capable of locating transition states (TSs) and minima and delivering a full reaction energy profile from 1D or 2D chemical representations. autodE is broadly applicable to study organic and organometallic reaction classes, including addition, substitution, elimination, migratory insertion, oxidative addition, and reductive elimination; it accounts for conformational sampling of both minima and TSs and is compatible with many electronic structure packages. The general applicability of autodE is demonstrated in complex multi‐step reactions, including cobalt‐ and rhodium‐catalyzed hydroformylation and an Ireland–Claisen rearrangement. Abstract : The program package autodE transforms mechanistic hypotheses from 2D chemical sketches to conformationally sampled 3D geometries using current computational best practices. Amongst other functions, autodE can generate full reaction profiles for complex reactions in a fully automated way.